Gold nanoparticles enlighten the future of cancer theranostics - Guo, Jianfeng; Rahme, Kamil; He, Yan; Li, Lin-Lin; Holmes, Justin; O'Driscoll, Caitriona (International journal of nanomedicine, 2017)
Development of multifunctional nanomaterials, one of the most interesting and advanced research areas in the field of nanotechnology, is anticipated to revolutionize cancer diagnosis and treatment. Gold nanoparticles (AuNPs) are now being widely utilized in bio-imaging and phototherapy due to their tunable and highly sensitive optical and electronic properties (the surface plasmon resonance). As a new concept, termed "theranostics," multifunctional AuNPs may contain diagnostic and therapeutic functions that can be integrated into one system, thereby simultaneously facilitating diagnosis and therapy and monitoring therapeutic responses. In this review, the important properties of AuNPs relevant to diagnostic and phototherapeutic applications such as structure, shape, optics, and surface chemistry are described. Barriers for translational development of theranostic AuNPs and recent advances in the application of AuNPs for cancer diagnosis, photothermal, and photodynamic therapy are discussed.